DAMPAK POLA ASUH ORANG TUA TERHADAP KARAKTER KEDISIPLINAN SISWA DI MI ROUDLOTUL JANNAH BUMIREJO KEPOHBARU(STUDI KASUS IBU SEBAGAI BURUH PABRIK AYAH SEBAGAI PETANI) - Anggraini, Ulfa Fitria; Shoimah, Retno Nuzilatus (-, 2026)
The role of parents in shaping children’s character, particularly discipline, is crucial for the success of education from an early age. The parenting style applied at home influences children’s behavior at school, including their adherence to rules, sense of responsibility, and independence. This study aims to identify the types of parenting styles adopted by parents and their impact on students’ disciplinary character at MI Roudlotul Jannah Bumirejo Kepohbaru. The research employed a qualitative approach with purposive sampling. The subjects consisted of six students whose mothers work as factory laborers and fathers as farmers. Data were collected through interviews, observations, and documentation. The findings revealed three types of parenting styles: democratic, authoritarian, and permissive. The democratic parenting style was the most dominant and had a positive impact on students’ discipline, as it fostered self-awareness in maintaining discipline. In contrast, the authoritarian style produced discipline through pressure rather than awareness, while the permissive style tended to have a negative impact on children’s discipline. These findings support the parenting theory of Dr. Paul Hauck and Elizabeth Hurlock’s theory of child character development. Based on the results, it is recommended that parents prioritize the democratic parenting style, which builds communication and self-awareness in children, to foster sustainable disciplinary character formation.